Exogenous hormone use, reproductive factors and risk of intrahepatic cholangiocarcinoma among women: results from cohort studies in the Liver Cancer Pooling Project and the UK Biobank - Petrick, Jessica L. (Br J Cancer, 2020)
BACKGROUND: Intrahepatic cholangiocarcinoma (ICC) arises from cholangiocytes in the intrahepatic bile duct and is the second most common type of liver cancer. Cholangiocytes express both oestrogen receptor-α and -β, and oestrogens positively modulate cholangiocyte proliferation. Studies in women and men have reported higher circulating oestradiol is associated with increased ICC risk, further supporting a hormonal aetiology. However, no observational studies have examined the associations between exogenous hormone use and reproductive factors, as proxies of endogenous hormone levels, and risk of ICC. METHODS: We harmonised data from 1,107,498 women who enroled in 12 North American-based cohort studies (in the Liver Cancer Pooling Project, LCPP) and the UK Biobank between 1980–1998 and 2006–2010, respectively. Cox proportional hazards regression models were used to generate hazard ratios (HR) and 95% confidence internals (CI). Then, meta-analytic techniques were used to combine the estimates from the LCPP (n = 180 cases) and the UK Biobank (n = 57 cases). RESULTS: Hysterectomy was associated with a doubling of ICC risk (HR = 1.98, 95% CI: 1.27–3.09), compared to women aged 50–54 at natural menopause. Long-term oral contraceptive use (9+ years) was associated with a 62% increased ICC risk (HR = 1.62, 95% CI: 1.03–2.55). There was no association between ICC risk and other exogenous hormone use or reproductive factors. CONCLUSIONS: This study suggests that hysterectomy and long-term oral contraceptive use may be associated with an increased ICC risk.